A meta-analysis of immunogenetic Case-Control Association studies in irritable bowel syndrome - Czogalla, Bastian; Mellein, Stefanie; Lorenzo Bermejo, Justo; Niesler, Beate (Journal of Neurogastroenterology and Motility, 2015)
Background: to date, genetic-association studies of single nucleotide polymorphisms (SNP) in selected candidate genes with the symptom phenotype of irritable bowel syndrome (IBS) have typically involved hundreds to 2000 patients. SNPs in immune-related genes, such as cytokine and cytokine receptor encoding genes, have been reported to associate with IBS risk. Methods: we conducted two independent case-control studies on 16 SNPs in IL1R1, IL4, IL6, IL8, IL10, IL23R, TNFA, and TNFSF15, one from the UK (194 patients and 92 healthy volunteers) and one from the USA (137 patients and 96 healthy volunteers). The main aim was to examine the relationship between inherited immunological diversity and IBS risk in a meta-analysis which included 12 additional, earlier studies. The meta-analysis comprised a total of 2894 patients (839 IBS-C, 1073 IBS-D, 502 IBS-M), and 3138 healthy volunteers with self-reported Caucasian ancestry. Key Results: the association of SNP rs4263839 (TNFSF15) was investigated in four studies and confirmed in the meta-analysis: IBS (OR 1.19, 95% CI 1.08-1.31), and IBS-C (OR 1.24, 95% CI 1.08-1.42). No additional SNPs residing in immunogenes associated with IBS symptom phenotypes. Conclusions & Inferences: our meta-analysis could not confirm a major role of most investigated SNPs, but a moderate association between rs4263839 TNFSF15 and IBS, in particular IBS-C. The analysis emphasizes the importance of definition and phenotype homogeneity, adequate study size and representativeness of the patient and control collective.